2017
DOI: 10.1007/s11368-017-1767-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic energy of anaerobic microbial redox reactions couples elemental biogeochemical cycles

Abstract: Purpose The thermodynamic energy of redox reactions affects the distribution of microbial redox reactions and cyclic transformation of elements in various anaerobic ecosystems. The principle of thermodynamics is of dramatic significance in understanding the energetics of metabolic processes, the biogeochemical behavior of microorganisms, and mass and energy cycles. The purpose of this paper is to relate the distribution of the coupling reactions between C, N, Fe, and S, the most important elements involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 107 publications
0
20
0
Order By: Relevance
“…Several strategies of Fe­(III) reducers could be utilized to facilitate the accessible solid iron as an electron acceptor, including direct cell–mineral contact, utilizing chelating agents or microbial/environmental redox-active electron shuttles, electron hopping, and microbial nanowires . Microbially catalyzed Feammox could potentially mobilize As via the reductive dissolution of sedimentary Fe­(III) minerals, which was recently evidenced by N and O isotopic analyses of nitrogen sources and nitrogen transformations in high As aquifers. , Thauera spp., associated with higher transcription levels in the groundwater-sourced (other than sediment-sourced) active microbial community, can use ammonium salts as the nitrogen source and reduce Fe­(III) oxides (such as Thauera humireducens SgZ-1), potentially supporting the Feammox process. ,, Sulfur disproportionation has also been evidenced by S and O isotopic analyses, critically causing As mobilization in the study area . S-Disproportionators ( Desulfurivibrio , Desulfobulbus , and Desulfocapsa ) were also more specifically active in groundwater-sourced than sediment-sourced microbial communities.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Several strategies of Fe­(III) reducers could be utilized to facilitate the accessible solid iron as an electron acceptor, including direct cell–mineral contact, utilizing chelating agents or microbial/environmental redox-active electron shuttles, electron hopping, and microbial nanowires . Microbially catalyzed Feammox could potentially mobilize As via the reductive dissolution of sedimentary Fe­(III) minerals, which was recently evidenced by N and O isotopic analyses of nitrogen sources and nitrogen transformations in high As aquifers. , Thauera spp., associated with higher transcription levels in the groundwater-sourced (other than sediment-sourced) active microbial community, can use ammonium salts as the nitrogen source and reduce Fe­(III) oxides (such as Thauera humireducens SgZ-1), potentially supporting the Feammox process. ,, Sulfur disproportionation has also been evidenced by S and O isotopic analyses, critically causing As mobilization in the study area . S-Disproportionators ( Desulfurivibrio , Desulfobulbus , and Desulfocapsa ) were also more specifically active in groundwater-sourced than sediment-sourced microbial communities.…”
Section: Resultsmentioning
confidence: 88%
“…22,66,67 Moreover, sulfate reduction can couple with ammonium oxidation (termed Surammox), producing reduced sulfur compounds (i.e., sulfide and/or element sulfur), which may facilitate As immobilization 68 and/or mobilization. 7,69 The significant variations in groundwater chemistry might infer diverse As-mobilizing N-, S-, As-, and Fe-related biogeochemical processes in the western Hetao basin aquifers studied here.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A new process for simultaneous anaerobic ammonium oxidation and sulfate reduction was observed for the first time by Fdz-Polanco et al (2001)during anaerobic treatment of vinassewho noticed that 50% of the nitrogen entering the reactor as total Kjeldahl nitrogen (TKN) was found as N 2 in the gas phase, and at the same time, 20% of the SO 4 2− originally present in the influent appears as S 2− in the effluent or H 2 S in the gas, with a sulfur removal efficiency of 80%. Fdz-Polanco et al (2001) proposed the following as a possible pathway: There is no evidence yet that anammox bacteria possess the ability to oxidize ammonium with sulfate as an electron donor (Wang et al, 2017;Bi et al, 2020). Other studies confirmed, nevertheless, the pathway described in Equation 13.13 (Yang et al, 2009;Rios-Del Toro et al, 2018) even at low temperatures (14-15°C) (Wu et al, 2020).…”
Section: Role Of Sulfur Compounds In Anaerobic Ammonium Oxidationmentioning
confidence: 99%